Greening Somerville. - Lechuga, Anthony; Lynch, Lauren; Ron, Sharon; Schwartz, Brooke; Smith, Cecilia; Sub, Gabriel. (Tufts University. Tisch Library., 2018)
2016 M.A. in Urban and Environmental Policy and Planning Field Project and Water: Systems, Science and Society Practicum. Client: Groundwork Somerville.